POLITICAL BUDGET CYCLES IN THE EUROPEAN UNION – POST-COMMUNIST HERITAGE - Wielechowski, Michał (Acta Scientiarum Polonorum. Oeconomia, 2018)
We test the hypothesis that post-communist history affect election cycles in the European Union countries. We show that pre-election fiscal manipulation increase total public spending per capita by 1.9% and three specific spending categories, i.e. general public services, public order and safety, and economic affairs in Central and Eastern Europe democracies with post-communist roots. At the same time we observe no significant spending deviations in remaining EU Member States, except expenditure linked to environmental protection. Our results indicate cross-country heterogeneity of political budget cycles (PBCs) in the EU, conditional on political system history.